Diagnostic accuracy of first‐trimester ultrasound in detecting abnormally invasive placenta in high‐risk women with placenta previa. (5th July 2018) - Cali, G.; Forlani, F.; Foti, F.; Minneci, G.; Manzoli, L.; Flacco, M. E.; Buca, D.; Liberati, M.; Scambia, G.; D'Antonio, F.
ABSTRACT: Objective: To ascertain the diagnostic accuracy of ultrasound in detecting abnormally invasive placenta (AIP) during the first trimester of pregnancy (11–14 weeks' gestation) in women at risk for this condition. Methods: This was a retrospective analysis of data collected prospectively from women at risk for AIP based upon the presence of at least one prior Cesarean section (CS) and/or uterine surgery and placenta previa, who had ultrasound assessment for AIP at the time of the 11–14‐week scan. The ultrasound signs explored in the present study were: loss of the clear zone, placental lacunae, bladder wall interruption and uterovesical hypervascularity. The potential of ultrasound and different ultrasound signs to predict the different types of AIP was assessed by computing summary estimates of sensitivity, specificity, diagnostic odds ratio (DOR) and positive (LR+) and negative (LR–) likelihood ratios. Results: One hundred and eighty‐eight women with placenta previa and at least one previous CS or uterine surgery were included in the study. All the explored ultrasound signs were associated significantly with the occurrence of AIP. Overall, when at least one ultrasound sign was used to make the diagnosis, ultrasound had a sensitivity of 84.3% (95% CI, 74.7–91.4%), specificity of 61.9% (95% CI, 51.9–71.2%), DOR of 8.6 (95% CI, 4.1–19.3), LR+ of 2.2 (95% CI, 1.7–2.9) and LR– of 0.3 (95% CI, 0.1–0.4) in detecting AIP. Using two ultrasound signs to label a case as positive increased the diagnostic accuracy in terms of specificity, although it did not affect sensitivity. Among the different ultrasound signs, loss of the clear zone had a sensitivity of 84.3% (95% CI, 74.7–91.4%) and a specificity of 81.9% (95% CI, 73.2–88.7%) in detecting AIP, while sensitivities for placental lacunae and bladder wall interruption were 78.3% (95% CI, 67.9–86.6%) and 75.9% (95% CI, 65.3–84.6%), respectively, and specificities were 81.0% (95% CI, 72.1–88.0%) and 99.1% (95% CI, 94.8–100.0%), respectively. The optimal combination of sensitivity and specificity was achieved when at least two imaging signs of AIP were used in the diagnostic algorithm. Conclusions: AIP can be detected from the first trimester of pregnancy in women at risk for this condition, and ultrasound performed between 11 and 14 weeks' gestation has an overall good diagnostic accuracy for detecting all types of AIP. However, these findings are applicable only to women with placenta previa and prior uterine scar. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations.